Open reduction combined with CORA-based osteotomy of the ulna in the treatment of missed Bado type I Monteggia injury: A retrospective study of 5 cases. Issue 47 (November 2017) - Xu, Zhenyu; Li, Yuchan; Wang, Zhigang; Cai, Haiqing
Abstract : Abstract: Open reduction combined with ulnar osteotomy is the most common approach to treating missed Monteggia injuries. The osteotomy is usually performed at the proximal ulna to ensure better healing and fewer complications. The purpose of this study is to present a center of rotation angulation (CORA)-based osteotomy of the ulna for treating Bado type I Monteggia injuries. We retrospectively reviewed the cases of patients who were treated with open reduction combined with a CORA-based ulnar osteotomy between February 2014 and December 2016. Each patient provided his or her internal control, and paired data of the involved and uninvolved sides were analyzed to evaluate forearm rotation function. Five patients (3 male, 2 female) with median age 5.7 years (range, 3.4–6.8 years) were operated on by the senior author in our hospital. The median interval between the original injury and the corrective surgery was 3 months (range, 1–4 months). In a median follow-up of 10 months (range, 6–17 months), all patients obtained stable reduction of the radial head and uneventful healing of the ulnar osteotomy. All patients had pain-free elbows with no neurological or vascular complications and no implant breakage. Patients showed excellent outcomes evaluated using the Broberg and Morrey index. Open reduction with a CORA-based osteotomy of the ulna for the treatment of missed Bado type I Monteggia injury with an obvious ulnar bowing deformity resulted in stable reduction of the radial head and excellent forearm function.